Energy audit of livestock production system in a mid-altitude Himalayan agro-ecosystem - RASTOGI, AKANKSHA; SINGH, KUNDAN; KUSHWAHA, GOVIND SINGH; SINGH, VIR (The Indian Journal of Animal Sciences, 2019)
The present study analyses energy flows through livestock production system and works out energy audit in selected mid-altitude villages in the Pithoragarh district of the Kumaun Division of Uttarakhand lying in the Central Himalayan region. The livestock population (converted into livestock units) consumed 144638094.9 kJ/day or 52792904649 kJ in a year and, in turn, produced 8490715137.07 kJ in a year through dung, 2056277724 kJ though milk, 60704289.30 kJ through calf crop and 6416.35 kJ by means of draught power supply to various agricultural operations. The gross energy produced by livestock was 10607703567 kJ/year. Proportion of the output energy from dung (80%) was much more than from milk (19%). Contribution of calf crop and draught animal power (DAP) was minimal compared to the overall energy. The gross energetic efficiency of livestock production was 20.09%. Energy for maintenance and growth available for livestock was 25.15%. The study reveals that a substantial proportion of energy in a mountain agro-ecosystem flows through livestock.